Expectation Gap Antara Persepsi Auditor Internal dan Auditee Terhadap Kinerja Auditor Internal Terkait dengan Pelaksanaan, Hasil, dan Tindak Lanjut Audit (Studi Pada Pemerintah Provinsi Maluku) - Nindya Felensia Simatauw (Master in Accounting Program, 2013)
This study aims to empirically examine the expectation gap between the perceptions of internal auditors and auditees on the performance of the internal auditors related to the audit, the audit results, and follow-up of audit.The technique of collecting data used questionnaires and documentation. Sampling in this study usied census techniques for internal auditors and purposive sampling techniques for the auditee. Analysis used the Mann-Whitney test.Based on the results of the test data and data analysis, it can be stated that there is expectation gap between the perceptions of internal auditors and auditees on the performance of the internal auditors related to the implementation audit and follow-up of audit. However, there is no expectation gap that was found between the perceptions of internal auditors and auditees on the performance of the internal auditors related to the audit results.